Current injection-based modeling of passive and active power filters in OpenDSS - Nien-Che Yang; Huai-Jan Liu; Chun-Jhih Yao; Imam Robandi (International Journal of Electrical Power & Energy Systems, 2025)
This study proposes active and passive filters based on current source models for use in power flow and harmonic flow studies. In a traditional power flow analysis, passive filters are modeled as impedance models incorporated into the bus impedance matrix and thus provide low impedance paths at resonant frequencies. However, extremely low impedance is associated with singular matrices and significant errors in harmonic power flow studies. The feasibility of the proposed modeling method is validated using the open-source power system analysis software open distribution system simulator (OpenDSS) for verification and comparison. For fundamental power flow calculations, voltage magnitude mismatches are limited to −0.0003 pu, and phase angle mismatches remain below −0.07°. In harmonic power flow calculations, maximum errors are observed at the 15th-order harmonic but remained minimal. Comparisons with the original single-tuned (ST) filter model in OpenDSS revealed current magnitude mismatches below 0.01% and phase angle mismatches within 0.1° for both fundamental and harmonic power flows. The limitations in OpenDSS for high-order damped power filter modeling were addressed via the proposed modeling method, including second-order damped (SD), third-order damped (TD), and C-type damped (CD) power filters.